Circulating Strains of Brucella abortus in Cattle in Santo Domingo De Los Tsáchilas Province – Ecuador - Rodríguez-Hidalgo, Richar Ivan; Contreras-Zamora, Javier; Benitez Ortiz, Washington; Guerrero-Viracocha, Karina; Salcan-Guaman, Holger; Minda, Elizabeth; Ron Garrido, Lenin (Frontiers in Public Health, 2015)
The Province of Santo Domingo de los Tsáchilas in Ecuador represents the largest informal cattle market. Because of its strategic position, cattle movement is very high and therefore we selected this region, to determine the strain variation of Brucella sp. Part of the study aimed at the isolation, biotyping, and genotyping of Brucella species from milk and supra-mammary lymph nodes of sero-positive bovines, using selective Farrell medium, biochemical assays, and IS711-PCR, AMOS-PCR, and HOOF-Prints techniques. In total, 656 animals from 12 sero-positive dairy herds and from the provincial slaughterhouse were diagnosed by Rose Bengal and Wright’s Slow Agglutination test with EDTA. Amongst these animals, 50 animals were sero-positive for brucellosis. Twenty-five lymph nodes and 25 milk samples from each group of positive reactors were transferred to culture medium. Isolation was possible from 4 (16%) lymph nodes and 9 (36%) milk samples; out of these, 10 isolates were diagnosed as Brucella sp. All four isolates of lymphatic tissue corresponded to Brucella abortus biotype 1, confirmed as field strains by molecular analysis. Milk isolations, showed biochemically a more dispersed pattern in which B. abortus biotypes 1 and 4 were found; yet four samples gave a pattern similar to B. abortus biotype 2; however, only biotypes 1 and 4 were confirmed by molecular analysis. The concordance between biochemical and molecular diagnostic tests reached 76.9%.